Informal Tradables and the Employment Growth of Indian Manufacturing - Ghani, Ejaz; Kerr, William R.; Segura, Alex (World Bank Group, Washington, DC, 2015)
India's manufacturing growth from 1989 to 2010 displays two intriguing properties: 1) a substantial fraction of absolute and net employment growth is concentrated in informal tradable industries, and 2) much of this growth is connected to the development of one-person establishments. This paper investigates the causes and determinants of these growth patterns. The rapid urbanization of the informal sector plays the strongest role, while there is some evidence for subcontracting by the formal sector and a "push" entrepreneurship story. The paper also finds modest connections of this growth to rising female labor force participation. The connection between the presence of informal manufacturing and local productivity levels is strong, and varies across urban and rural areas in ways that bolster urbanization and subcontracting hypotheses.